Printing systems and methods including multilayer films

JP2025028881AActive Publication Date: 2025-03-05DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024196273
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-05-02
Filing Date
2024-11-08
Publication Date
2025-03-05
Estimated Expiration
2040-04-27

Smart Images

  • Figure 2025028881000001
    Figure 2025028881000001
  • Figure 2025028881000002
    Figure 2025028881000002
  • Figure 2025028881000003
    Figure 2025028881000003
Patent Text Reader

Abstract

To provide printing systems including multilayer films that achieve proper wetting and anchoring of ink compositions without requiring additional primer layer or corona or plasma treatments.SOLUTION: The present invention relates to printing systems and methods that may include an ink composition including electrically charged ink particles dispersed in a hydrocarbon liquid and a multilayer film. The multilayer film may include a polymeric core layer; and one or more printing layers adjacent to the polymeric core layer. The one or more printing layers may include at least 50 wt.% of an ethylene vinyl acetate copolymer having acid and acrylate functional groups. The ethylene vinyl acetate copolymer having acid and acrylate functional groups may include from 0.5 wt.% to 4 wt.% methacrylic or acrylic acid; from 0.5 wt.% to 4 wt.% acrylate, from 7 wt.% to 40 wt.% vinyl acetate; and the balance ethylene, based on the total weight of the ethylene vinyl acetate copolymer having acid and acrylate functional groups.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation of U.S. Provisional Patent Application No. 62 / 842,012, filed May 2, 2019. No. 60 / 339,933, filed on Oct. 23, 2003, the disclosure of which is hereby incorporated by reference in its entirety.

[0002] The embodiments described herein relate generally to multilayer films, and in particular to digital printing systems. This relates to multilayer films utilized in systems. [Background technology]

[0003] In recent years, the printing process of digital printing machines has had an impact on the graphic arts market. In traditional printing methods using fixed, etched plates, the ink is The ink is attracted to the substrate by the physical transfer of the ink from the ink tray to the cylinder. In the printing process of a cylinder press, the ink composition is transferred physically from the ink tray to the cylinder. Instead of moving randomly, they are attracted to the photographic imaging plate by an electric charge. Summary of the Invention

[0004] In the digital printing process, inks containing ethylene and acrylic copolymers are used. The ink compositions are then heated and applied to a substrate such as a flexible film. As with conventional printing presses, the printing process in digital printing presses involves applying liquid ink to the However, in the digital printing process, the ink is electrostatically charged. The particles are attracted to an electrostatic field established on a photographic imaging plate. When the ink composition is disposed on a photographic imaging plate, the disposed ink composition Direct contact between the heated blanket and the ink composition on the photographic imaging plate The ink is transferred directly to the heated blanket by the The ink particles of the ink composition melt into a smooth ink film that is then transferred onto the substrate. will be done.

[0005] In the printing process of conventional digital printers, overprint varnish (OPV) or utilizes a lamination process to bond the printed material (transfer In addition, the printing process of conventional digital printers protects the ink film that is transferred onto the paper. Corona-treated film is used to provide proper wetting and fix the printed artwork. It is often necessary to apply a primer over the , increased process complexity, increased costs associated with the process, and internal / external (wrapping There are drawbacks including poor sealing when a pressure seal is required for the package design. do.

[0006] Therefore, no additional primer layer or corona or plasma treatment is required. A printing system utilizing a multi-layer film that achieves proper wetting and fixation of the ink composition. There is a need for a method for applying an ink composition during a digital printing process. A multi-layer film including an ink fixing layer ("printing layer") that can be wetted and fixed properly. The multilayer film also meets these needs by providing a core layer This allows the multilayer film to exhibit the appropriate stiffness and maintain the appropriate dimensions. It can be printed using a digital printer line.

[0007] In accordance with at least one embodiment of the present disclosure, a printing system is provided. An embodiment of the system includes an ink composition including electrically charged ink particles dispersed in a liquid, and a multi-layer ink. The multilayer film may include a polymer core layer and a polymer layer adjacent to the polymer core layer. The one or more printed layers may include at least 50% by weight of an acid and and ethylene vinyl acetate copolymers having acrylate functional groups. The acrylate-functional ethylene vinyl acetate copolymer is a copolymer having both acid and acrylate functionality. 0.5% to 4% by weight based on the total weight of the ethylene vinyl acetate copolymer having the group of methacrylic acid or acrylic acid, 0.5% to 4% by weight of acrylate, 7% to It may contain 40% by weight vinyl acetate, and the remainder ethylene.

[0008] In accordance with at least one embodiment of the present disclosure, a printing method is provided. Embodiments may include transferring the ink composition to a print layer of a multilayer film. The article may include electrically charged ink particles dispersed in a liquid. a polymeric core layer and one or more printed layers adjacent the polymeric core layer, the one or more printed layers comprising: At least 50% by weight of an ethylene vinyl acetate copolymer having acid and acrylate functional groups. The ethylene vinyl acetate copolymers containing the monomers and having acid and acrylate functional groups are Based on the total weight of ethylene vinyl acetate copolymer having acid and acrylate functional groups , 0.5% to 4% by weight of methacrylic acid or acrylic acid, 0.5% to 4% by weight of acrylate, 7% to 40% by weight vinyl acetate, and the balance ethylene.

[0009] Thus, embodiments of the present disclosure may include an additional primer layer or a corona or plasma Proper wetting and fixation of ink compositions during the digital printing process without the need for pretreatment It is possible to provide a printing system and method that can achieve the above.

[0010] These and other embodiments are described in more detail below in the Detailed Description of the Invention. Please provide more details. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Certain embodiments of the present application will now be described. These embodiments are provided for purposes of illustration only and are not intended to be limiting unless otherwise specified. This disclosure is provided so as to be comprehensive and complete, and to fully convey the scope of the subject matter to those skilled in the art.

[0012] The term "polymer" refers to any combination of monomers, whether of the same or different types. It refers to a polymeric compound prepared by polymerizing the following: Polymer includes the term "homopolymer," which is usually a polymer that is made up of one type of monomer. "Copolymer" refers to a polymer prepared exclusively from two or more different monomers. As used herein, the term "interpolymer" refers to a polymer prepared from The term refers to polymers prepared by polymerization of at least two different types of monomers. Thus, the general term interpolymer refers to more than two polymers, such as terpolymers. The term "polymer" includes copolymers or polymers prepared from different types of monomers.

[0013] As used herein, an "acid copolymer" refers to a direct copolymer or a graft copolymer. The term "direct copolymer" refers to a copolymer in which the monomer is bonded to an existing polymer chain. Unlike graft copolymers, which are polymerized in a single step, It may also refer to a copolymer made by

[0014] "Polyethylene" or "ethylene-based polymer" refers to polymers that contain units derived from ethylene monomers. By this we mean polymers containing more than 50 mol % of ethylene. The term "polymer" includes a mer or copolymer (meaning units derived from two or more comonomers). A common form of ethylene-based polymer known in the art is low density polyethylene. (LDPE), Linear Low Density Polyethylene (LLDPE), Ultra Low Density Polyethylene (Ul tra Low Density Polyethylene (ULDPE), ultra-low density Polyethylene (Very Low Density Polyethylene:VLD PE), and synthetic low density resins including both linear and substantially linear low density resins (m-LLDPE). Glucite catalyzed linear low density polyethylene, medium density polyethylene (MDPE), and and high density polyethylene (HDPE). Copolymers are produced in polymer technology using either autoclaves or tubular reactors. The copolymers may be prepared by well-known processes. Nos. 72, 4,351,931, 4,248,990, and 5,028,67 As disclosed in International Patent Application No. 99 / 25742, the autoclave The process can be carried out as a continuous process within a reactor.

[0015] Ethylene vinyl acetate (EVA) is a copolymer of ethylene and vinyl acetate. An example of an EVA copolymer is available from DuPont Company, Wilmington, Del. It is available from several sources, including

[0016] Ethylene / acid copolymers and methods for their preparation are well known in the art, e.g. For example, U.S. Patent Nos. 3,264,272, 3,404,134, and 3,355,31 9, and 4,321,337. Suitable commercially available acid copolymers are available from DuPont Company, Wilmington, It is available from a variety of sources, including Del.

[0017] The term "LDPE" stands for "high pressure ethylene polymer" or "highly branched poly The polymer is sometimes referred to as "ethylene" and is reacted with a free radical initiator such as a peroxide. By using the It is partially or completely homopolymerized or copolymerized in a clave or tubular reactor. (See, e.g., U.S. Pat. No. 6,349,363, which is incorporated herein by reference) (See US Pat. No. 4,599,392.) LDPE resins typically have a viscosity of 0.916 to 0. It has a density in the range of .940 g / cc.

[0018] The term "LLDPE" includes resins made using Ziegler-Natta catalyst systems. These include resins made using bismetallocene catalysts, and resins made using single-site catalysts. (sometimes referred to as "m-LLDPE"), phosphinimines, constrained geometry catalysts, and These include, but are not limited to, resins made using metallocene and post-metallocene catalysts. Bis(biphenylphenoxy) catalysts (also called polyaryloxy ether catalysts) LLDPE includes, but is not limited to, linear, substantially linear, or heterogeneous ethylene-based copolymers or homopolymers. E, and U.S. Pat. No. 5,272,236 and U.S. Pat. No. 78,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,15 No. 3,663,675; and substantially linear ethylene polymers as further defined in U.S. Pat. No. 3,663,675. homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 45,992; Heterogeneous branching, such as that prepared according to the process disclosed in US Pat. No. 4,076,698. Ethylene polymers, blends thereof (U.S. Pat. No. 3,914,342 and U.S. Pat. No. 5,313,633) The LLDPE resins include those disclosed in US Pat. No. 5,854,045. Any type of reactor or reactor configuration known in the art may be used to produce gas phase, liquid phase, or , or slurry polymerization, or any combination thereof.

[0019] "Multilayer structure" means any structure having two or more layers. For example, a multilayer structure (e.g., a film) may have two, three, four, five, or more layers. A layer structure may be described as having layers designated by letters. For example, a layer structure designated A / B / C may be described as having layers designated by letters. A three-layer structure may have a core layer B and two outer layers A and C. Similarly, two A structure with core layers B and C and two outer layers A and D is designated A / B / C / D. In some embodiments, the multilayer films of the present disclosure include at least two layers. In some embodiments, the multilayer films of the present disclosure include up to 15 layers.

[0020] Reference will now be made in detail to embodiments of a printing system. As previously mentioned, the present invention relates to a printing system. Embodiments of the printing system may include an ink composition and a multilayer film.

[0021] Reference will now be made in detail to embodiments of the ink compositions of the printing system. The ink may include electrically charged ink particles dispersed in a liquid. The particles of the ink composition are then transferred onto a photographic imaging plate during the digital printing process. The attraction of charged particles to electrostatic fields. The force precisely positions the ink composition on the photographic imaging plate and then The multilayer film can be transferred to a substrate such as the multilayer film embodiments described herein.

[0022] The charged ink particles may include one or more pigments and a resin material. The ink composition may include about fluoropolymer resin, based on the total weight of the ink composition. 0.001% to about 2%, or about 0.001% to about 1% by weight of fluoropoly The one or more pigments of the charged ink particles may include a pigment resin, which is known in the art of digital printing. The ink composition may include a pigment that is about 0. 0.001% to about 5% by weight, or about 0.001% to about 2.5% by weight of one or more This may include fees.

[0023] As previously mentioned, the charged ink particles can be dispersed in a liquid. In an embodiment, the charged ink particles are In some embodiments, the liquid may be a hydrocarbon liquid. In a further embodiment, the hydrocarbon liquid may comprise a petroleum hydrocarbon. , less than about 90 wt. % or less than about 80 wt. % liquid based on the total weight of the ink composition. It may include.

[0024] Reference will now be made in detail to the multilayer film embodiment of the printing system. , a polymeric core layer, and one or more printed layers adjacent to the polymeric core layer. Although not limited to the above, one or more of the printed layers of the multilayer film may be coated with an additional primer layer. Or the ink composition is applied during the digital printing process without the need for corona or plasma treatment. It is believed that this may allow for proper wetting and immobilization of the composition. However, the polymer core layer of the multilayer film may provide adequate stiffness so that the multilayer film can be It is believed that the system can be printed on a digital printer line with proper dimensions.

[0025] In one or more embodiments, the multilayer film may include at least two layers. In some embodiments, the multilayer films of the present disclosure include up to 15 layers. Multilayer films are available in 2-15 layers, 2-10 layers, 2-5 layers, 5-15 layers, and 5- It may contain 10 layers, or between 10 and 15 layers.

[0026] In a further embodiment, the multilayer film may be a two-layer structure designated A / B and may be printed. The printing layer may be designated A and the polymer core layer may be designated B. In other embodiments, multiple The layered film may be a three layer construction designated A / B / C, with the polymer core layer designated B. and the printed layers may be designated A and C.

[0027] As previously mentioned, embodiments of the multilayer film may include a polymer core layer. In embodiments, the polymer core layer may be polyethylene terephthalate, polyamide, ethylene The polymer may include one or more of a propylene-based polymer, a propylene-based polymer, or a combination thereof. In embodiments, the polymer core layer comprises an ethylene-based polymer. In some embodiments, the polymer core layer may contain greater than 50 mole percent units derived from ethylene monomers. In a further embodiment, the polymer core layer is an ethylene-based homopolymer or copolymer. Embodiments of the polymer core layer may include low density polyethylene (LDPE), linear Linear low density polyethylene (LLDPE), ultra low density polyethylene (Ultra Low Ultra-low density polyethylene (ULDPE), ultra-low density polyethylene (V ery Low Density Polyethylene:VLDPE), linear and and substantially linear low density resin (m-LLDPE) Linear low density polyethylene, medium density polyethylene (MDPE), and high density polyethylene Examples of such polymers include, but are not limited to, polyethylene (HDPE).

[0028] In an embodiment, the polymer core layer has a 2% secant modulus of greater than about 150 MPa. In some embodiments, the polymer core layer may comprise an ethylene-based polymer having a molecular weight of about 15 The polymer may include an ethylene-based polymer having a 2% secant modulus of from 0 MPa to about 1500 MPa. In other embodiments, the polymer core layer has a compressive strength of about 150 MPa to about 1000 MPa, about 150 MPa ~ approx. 750 MPa, approx. 150 MPa ~ approx. 500 MPa, approx. 150 MPa ~ approx. 250 MPa, approx. 250MPa ~ approx. 1500MPa, approx. 250MPa ~ approx. 1000MPa, approx. 2 50MPa ~ approx. 750MPa, approx. 250MPa ~ approx. 500MPa, approx. 500MPa ~ approx. 1 500MPa, approx. 500MPa to approx. 1000MPa, approx. 500 to approx. 750MPa, approx. 75 0MPa to about 1500MPa, about 750MPa to about 1000MPa, or about 1000M The composition may include an ethylene-based polymer having a 2% secant modulus of elasticity of about 1500 MPa to about 1500 MPa. Without being bound by theory, the stiffness of the polymer core layer is determined by the dimensional stability during the digital printing process. It is believed that this could enable legal certainty.

[0029] In some embodiments, the polymeric core layer has a viscosity measured according to ASTM D792. In the case of 10 ... 3 ) ~ approx. 0.965g / cm 3 In some embodiments, the polymer core layer may have a density of about 0.865 g / cm 3 ~Approx. 0.945g / cm 3 , about 0.865g / cm 3 ~Approx. 0.925g / cm 3 , about 0.865g / cm 3 ~Approx. 0.905g / cm 3 , about 0.865g / cm 3 ~about 0 .885g / cm 3 , about 0.885g / cm 3 ~Approx. 0.965g / cm 3 , about 0.885 g / cm 3 ~Approx. 0.945g / cm 3 , about 0.885g / cm 3 ~Approx. 0.925g / cm 3 , about 0.885g / cm 3 ~Approx. 0.905g / cm 3 , about 0.905g / cm3 ~about 0 .965g / cm 3 , about 0.905g / cm 3 ~Approx. 0.945g / cm 3 , about 0.905 g / cm 3 ~Approx. 0.925g / cm 3 , about 0.925g / cm 3 ~Approx. 0.965g / cm 3 , about 0.925g / cm 3 ~Approx. 0.945g / cm 3 , or about 0.945 g / cm 3 ~Approx. 0.965g / cm 3 The density of the sintered body may be 0.01 to 0.01.

[0030] The polymer core layer is measured at 190°C and 2.16 kg according to ASTM D1238. When the melting point is set at about 0.1 grams per 10 minutes (g / 10 min) to about 45.0 g / 10 min, In some embodiments, the polymer core layer may have a flow rate of about 0.2 g / 10 minutes ~ approx. 40.0g / 10 minutes, approx. 0.2g / 10 minutes ~ approx. 30.0g / 10 minutes, approx. 0.2 g / 10 minutes ~ approx. 20.0 g / 10 minutes, approx. 0.2 g / 10 minutes ~ approx. 10.0 g / 10 minutes, approx. 0 .2g / 10 minutes ~ approx. 1.0g / 10 minutes, approx. 1.0g / 10 minutes ~ approx. 45.0g / 10 minutes, approx. 1.0g / 10 minutes ~ approx. 30.0g / 10 minutes, approx. 1.0g / 10 minutes ~ approx. 20.0g / 10 minutes , about 1.0g / 10 minutes to about 10.0g / 10 minutes, about 1.0g / 10 minutes to about 5.0g / 10 min, approx. 10g / 10 min ~ approx. 45.0g / 10 min, approx. 10.0g / 10 min ~ approx. 20.0g / 10 minutes, about 10.0g / 10 minutes to about 15.0g / 10 minutes, about 15.0g / 10 minutes to about 40 0.0g / 10min, or melt flow rate of about 15.0g / 10min to about 20.0g / 10min It may have a port.

[0031] Various commercial embodiments are contemplated as suitable for the polymer core layer. For example, The polymer core layer is commercially available from The Dow under the trademark DOWLEX™ GM 8070. Linear low density ethylene-based polymers available from Chemical Company may include.

[0032] In some embodiments, the polymer core layer has a thickness of from about 10 microns to about 445 microns. In other embodiments, the polymer core layer may be about 10 micrometers (micrometers). 10 microns to about 200 microns, about 10 microns to about 300 microns, about 10 microns to about 2 00 microns, about 10 microns to about 100 microns, about 100 microns to about 445 microns 100 microns to 400 microns, 100 microns to 300 microns, 1 00 microns to about 200 microns, about 200 microns to about 445 microns, about 200 microns Ron ~ approx. 400 microns, approx. 200 microns ~ approx. 300 microns, approx. 300 microns ~ approx. 445 microns, about 300 microns to about 400 microns, or about 400 microns to about 4 It can be 45 microns.

[0033] Reference will now be made in detail to embodiments of one or more printed layers of the multilayer films described herein. As mentioned above, without wishing to be bound by theory, one or more prints of the multi-layer film The layer is digitally applied without the need for an additional primer layer or corona or plasma treatment. It is believed that this may allow for proper wetting and fixing of the ink composition during the printing process.

[0034] In embodiments, one or more of the printed layers may comprise an ethylene oxide polymer having acid and acrylate functional groups. Includes vinyl acetate copolymers. Ethylene vinyl acetate with acid and acrylate functional groups. The copolymers are copolymers of ethylene with vinyl acetate, acrylate, and acid comonomers. or by blending two or more copolymers or terpolymers. directly, by grafting, or by other methods known in the art. In some embodiments, the acid and acrylate functional groups can be produced by ethylene acetate. In another embodiment, the acid and acrylate functional groups may be grafted onto a vinyl polymer backbone. The functional group is an ethylene vinyl acetate polymer having an acid group, an acrylate group, or both. This can be achieved by blending with one or more polymers that are In the form, ethylene vinyl acetate copolymers having acid and acrylate functional groups are The vinyl acetate polymer is then mixed with an ethylene copolymer having acid groups, acrylate groups, or both. The polymer or terpolymer may be melt blended with the polymer or terpolymer. In this state, ethylene vinyl acetate polymer is ethylene (C3-C10) alkyl acrylate. and ethylene monocarboxylic acid copolymers. The acid may include acrylic acid or methacrylic acid. In another embodiment, ethylene vinyl acetate. The copolymer may be blended with an ethylene alkyl acrylate monocarboxylic acid terpolymer. In one embodiment, the ethylene alkyl acrylate monocarboxylic acid terpolymer is Ethylene vinyl acetate polymers. - approximately 0.05% when measured at 190°C and 2.16 kg according to ASTM D1238 .5g / 10 minutes ~ approx. 10g / 10 minutes, approx. 1g / 10 minutes ~ approx. 10g / 10 minutes, approx. 2g / 10 Melt index: approx. 10g / 10min, or approx. 5g / 10min to approx. 10g / 10min The ethylene alkyl acrylate copolymer or terpolymer may have the formula: Approximately 0.5g / 10min when measured at 190°C and 2.16kg according to D1238 ~Approx. 15g / 10 minutes, approx. 1g / 10 minutes ~ approx. 15g / 10 minutes, approx. 5g / 10 minutes ~ approx. 15g / 10 minutes, or from about 10 g / 10 minutes to about 15 g / 10 minutes.

[0035] Without wishing to be bound by theory, it is believed that the ethylene acetate having acid and acrylate functional groups Vinyl acid copolymers do not require an additional primer layer or corona or plasma treatment. may allow for proper wetting and fixation of the ink composition during the digital printing process without In an embodiment, ethylene vinyl acetate having acid and acrylate functionality is The copolymer is a total of ethylene vinyl acetate copolymers having acid and acrylate functional groups. Based on weight, about 0.5% to about 4% by weight of methacrylic acid or acrylic acid, about 0. 5% to about 4% by weight of acrylate, about 10% to about 40% by weight of vinyl acetate, and and the remainder ethylene.

[0036] Based on the total weight of ethylene vinyl acetate copolymer having acid and acrylate functional groups In some embodiments, ethylene vinyl acetate having acid and acrylate functional groups is used. The copolymer may contain from about 0.5% by weight to about 4% by weight of methacrylic acid or acrylic acid, or about 0.5% by weight to about 3% by weight, about 0.5% by weight to about 2% by weight, about 0.5% by weight to about 1% by weight Amount%, about 1% to about 4% by weight, about 1% to about 3% by weight, about 1% to about 2% by weight, about 2% to about 4% by weight, or about 3% to about 4% by weight of methacrylic acid or acrylic It may contain an acid.

[0037] In an embodiment, an ethylene vinyl acetate copolymer having acid and acrylate functional groups. The acrylate is an alkyl acrylate having 1 to 4 carbon atoms in the alkyl portion. In a further embodiment, the acrylate may include methyl acrylate, ethyl acrylate, acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate In other embodiments, the acid and acrylate may include isobutyl acrylate. The acrylate of the ethylene vinyl acetate copolymer having the functional group is methyl methacrylate. methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, n- Hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate methacrylic acid such as methacrylate, n-decyl methacrylate, and dodecyl methacrylate. It may include alkyl esters. Ethylene vinyl acetate with acid and acrylate functional groups. Based on the total weight of the copolymer, in some embodiments, the acid and acrylate functional groups The ethylene vinyl acetate copolymer having about 0.5% to about 4% by weight of an acrylate or about 0.5% by weight to about 3% by weight, about 0.5% by weight to about 2% by weight, about 0.5% by weight to About 1% by weight, about 1% to about 4% by weight, about 1% to about 3% by weight, about 1% to about 2% by weight %, about 2% to about 4% by weight, or about 3% to about 4% by weight of acrylate. do.

[0038] Based on the total weight of ethylene vinyl acetate copolymer having acid and acrylate functional groups In some embodiments, ethylene vinyl acetate having acid and acrylate functional groups is used. The copolymer may be from about 7% by weight to about 40% by weight of vinyl acetate, or from about 7% by weight to about 30% by weight of vinyl acetate. Amount%, about 7% to about 20% by weight, about 7% to about 10% by weight, about 10% to about 40% by weight Amount%, about 10% to about 30% by weight, about 10% to about 20% by weight, about 20% to about 4 0% by weight, about 20% by weight to about 30% by weight, or about 30% by weight to about 40% by weight of bis(trimethylsilyl)acetate. It may contain nyl.

[0039] Ethylene vinyl acetate copolymers with acid and acrylate functional groups are classified according to ASTM Approximately 0.890 grams per cubic centimeter (g / cm 3 ) ~ approx. 0.985g / cm 3 In some embodiments, the acid and and acrylate-functional ethylene vinyl acetate copolymers have a density of about 0.890 g / cm 3 ~Approx. 0.980g / cm 3 , about 0.890g / cm 3 ~Approx. 0.960g / cm 3 , about 0 .890g / cm 3 ~Approx. 0.940g / cm 3 , about 0.890g / cm 3 ~about 0.920 g / cm 3 , about 0.890g / cm 3 ~Approx. 0.900g / cm 3 , about 0.900g / cm 3 ~Approx. 0.985g / cm 3 , about 0.900g / cm 3 ~Approx. 0.960g / cm 3 , about 0 .900g / cm 3 ~Approx. 0.940g / cm 3 , about 0.900g / cm 3 ~about 0.920 g / cm 3 , about 0.920g / cm 3 ~Approx. 0.985g / cm 3 , about 0.920g / cm 3 ~Approx. 0.960g / cm 3 , about 0.920g / cm 3 ~Approx. 0.940g / cm 3 , about 0 .940g / cm 3 ~Approx. 0.985g / cm 3 , about 0.940g / cm 3 ~about 0.960 g / cm 3 , or about 0.960 g / cm 3 ~Approx. 0.985g / cm 3 may have a density of .

[0040] Ethylene vinyl acetate copolymers with acid and acrylate functional groups are classified according to ASTM Approximately 0.5 per 10 minutes when measured at 190°C and 2.16 kg according to D1238 The melt flow rate may range from about 1.5 g / 10 min to about 20.0 g / 10 min. In some embodiments, an ethylene vinyl acetate copolymer having acid and acrylate functional groups is used. Approximately 0.5g / 10 minutes to approximately 20g / 10 minutes, approximately 0.5g / 10 minutes to approximately 15.0g / 10 minutes min, approx. 0.5g / 10 min ~ approx. 10.0g / 10 min, approx. 0.5g / 10 min ~ approx. 5.0g / 1 0 minutes, about 0.5g / 10 minutes to about 1.0g / 10 minutes, about 1.0g / 10 minutes to about 20g / 10 min, approx. 1.0g / 10 min ~ approx. 15.0g / 10 min, approx. 1.0g / 10 min ~ approx. 10.0g / 10 minutes, approx. 1.0g / 10 minutes ~ approx. 5.0g / 10 minutes, approx. 5.0g / 10 minutes ~ approx. 20.0g / 10 minutes, approx. 5.0g / 10 minutes ~ approx. 15.0g / 10 minutes, approx. 5.0g / 10 minutes ~ approx. 10. 0g / 10 minutes, approx. 10.0g / 10 minutes ~ approx. 20.0g / 10 minutes, approx. 10.0g / 10 minutes ~ Approximately 15.0g / 10min, or approximately 15.0g / 10min to approximately 20.0g / 10min Melt-Fill It may have a low rate.

[0041] In some embodiments, one or more of the printed layers may comprise a polyolefin and an acid and acrylic. The present invention may include blends with ethylene vinyl acetate copolymers having rate functionality. In the present invention, the one or more printed layers are at least 50% by weight based on the total weight of the one or more printed layers. % of an ethylene vinyl acetate copolymer having acid and acrylate functional groups. Without wishing to be bound by theory, it is believed that the polyolefin and the functionalized ethylene polymer are miscible. It is believed that the polymers are not interfacial and may form separate phases when blended. At least 50% by weight of an ethylene vinyl acetate copolymer having acid and acrylate functional groups. The inclusion of a polymer allows the formation of an ethylene vinyl acetate copolymer having acid and acrylate functionality. The polymer may be the continuous phase in the blend and may be incorporated into one or more printed layers of the digital ink composition. In some embodiments, one or more of the printed layers may be , about 50% to about 100% by weight, about 50% to about 80% by weight, about 50% to about 60% by weight Weight%, approx. 60% to approx. 100%, approx. 60% to approx. 80%, approx. 80% to approx. Approximately 100% by weight of an ethylene vinyl acetate copolymer having acid and acrylate functional groups It may include.

[0042] Polyolefins and ethylene vinyl acetate copolymers with acid and acrylate functional groups. In embodiments of one or more printed layers that include a blend with a mer, the blend may include an acid and acrylate functional group. Polyolefins blended with ethylene vinyl acetate copolymers having the formula They are produced using homogeneous or heterogeneous catalyst systems and a variety of commercial polymerization processes known in the art. In an embodiment, an ethylene vinyl acetate copolymer having acid and acrylate functional groups is obtained. Polyolefin blended with cellulose has a viscosity of about 0.865 g / cm 3 ~Approx. 0.940g / cm 3 In other embodiments, esters having acid and acrylate functional groups may have a density in the range of 100 to 2000 nm. Polyolefin blended with ethylene vinyl acetate copolymer has a viscosity of about 0.865 g / cm 3 ~Approx. 0.940g / cm 3 , about 0.865g / cm 3 ~Approx. 0.920g / cm 3 , about 0 .865g / cm 3 ~Approx. 0.900g / cm 3 , about 0.865g / cm 3 ~about 0.880 g / cm 3 , about 0.880g / cm 3 ~Approx. 0.940g / cm 3 , about 0.880g / cm 3 ~Approx. 0.920g / cm 3 , about 0.880g / cm 3 ~Approx. 0.900g / cm 3 , about 0 .900g / cm 3 ~Approx. 0.940g / cm 3 , about 0.900g / cm 3 ~about 0.920 g / cm 3 , or about 0.920 g / cm 3 ~Approx. 0.940g / cm 3 may have a density of .

[0043] In a further embodiment, ethylene vinyl acetate copolymers having acid and acrylate functional groups are used. Polyolefins blended with polymers include low density polyethylene (LDPE), Linear low density polyethylene (LLDPE), ultra low density polyethylene (Ultra Low Ultra-low density polyethylene (ULDPE) Very Low Density Polyethylene (VLDPE), linear and substantially linear low density resin (m-LLDPE) containing both single-site catalyst Linear low density polyethylene, medium density polyethylene (MDPE), and high density polyethylene (HDPE) Examples of suitable ethylene include, but are not limited to, ethylene (HDPE). In certain embodiments, One or more of the printed layers may comprise LLDPE. LLDPE has Approximately 0.915 grams (g / cm 3 ) ~ approx. 0.955g / cm 3 , 0.915g / cm 3 ~Approx. 0.945g / cm 3 , 0.915g / cm 3 ~Approx. 0.935g / cm 3 , 0.91 5g / cm 3 ~Approx. 0.925g / cm 3 LLDPE can have a density of about 0.70 g / 10 min to approx. 1.0 g / 10 min, approx. 0.80 g / 10 min to approx. 1.0 g / 10 min, or approx. The ethylene-based polymer may have a melt index of 0.90 to about 1.0 g / 10 min. Various commercial embodiments provide acid and acrylate functional groups for use in one or more printed layers. It is believed to be suitable for blending with ethylene vinyl acetate copolymers having For example, a suitable ethylene-based polymer is available under the trade name DOWLEX™ GM 8070. Available commercially from The Dow Chemical Company under the terms of the following publications:

[0044] Embodiments of the printing system may optionally include one or more additional layers. In the , one or more additional layers may be a sealing layer, a barrier layer, a tie layer, or a combination thereof. This may include a combination of

[0045] In some embodiments, the printing system optionally includes one or more sealing layers. Without wishing to be bound by theory, one or more sealing layers may be The structure is heat sealable, contains the product, and retains one or more optional barrier layers. Various commercial embodiments may be suitable for one or more sealing layers. For example, a suitable sealing layer is disclosed in The Dow Chemical AFFINITY PL 1888G, ELITE (TM) from Al Company Commercially available as DOWLEX(TM) 5401G, DOWLEX(TM) 2045, and LDPE 611A. obtain.

[0046] In some embodiments, the printing system optionally includes one or more barrier layers. In an embodiment, the one or more core layers are formed of one or more print layers and one or more barrier layers. Without wishing to be bound by theory, it is believed that one or more of the barrier layers may be chemically resistant. It may provide chemical resistance and help prevent the transmission of moisture, light, and oxygen. The one or more barrier layers may be one or more of polyamide, ethylene vinyl alcohol, or Various commercial embodiments may include one or more For example, a suitable sealing layer is U LTRAMID C33, EVAL from Kuraray, SK Chemicals SARAN from the Dow Chemical Company, and E It may be commercially available as LITE™ 5960G and XUS 59900.94.

[0047] In some embodiments, the printing system optionally includes a polyolefin-based film. The adhesive may include one or more tie layers that can adhere to one or more barrier layers. Suitable tie layers are BYNEL™ 41E710 and AMPLIFY™ TY 1 It can be commercially available as 451B.

[0048] Reference will now be made in detail to embodiments of printing methods that utilize the printing systems described herein. do.

[0049] As previously mentioned, embodiments of the printing methods described herein include applying the ink composition to a multi-layer film. The ink composition may include transferring the ink to a printing layer of the inkjet printer. The multilayer film may include a polymer core layer and a polymer core layer having ink particles. The print layer may include one or more adjacent printed layers, and the one or more printed layers may include at least 50% by weight of an acid. and ethylene vinyl acetate copolymers having acrylate functionality.

[0050] In an embodiment, the printing method may utilize a digital printing press. Various commercial embodiments of the machine are believed to be suitable. For example, a suitable digital printing machine The machine may be commercially available from HP under the trademark Indigo™.

[0051] During digital printing, a laser array is used to print a photosensitive photographic imaging plate. In an embodiment, the image to be printed on the paper (i.e., the print image) can be constructed as follows: The printed image may be constructed on a photographic imaging plate as an electrostatic field. Charged particles can be attracted to the electrostatic field established on a photographic imaging plate. The charged particles of the ink composition can then be deposited on a photographic imaging plate. In traditional printing methods using coated and etched plates, the ink is transferred to the ink tray. The ink is attracted to the substrate by the physical transfer of the ink from the nozzle to the cylinder. In the embodiment of the printing method described above, the ink composition is physically transferred from the ink tray to the cylinder. Instead of moving, they are attracted to the photographic imaging plate by their electric charge.

[0052] Once the ink composition has been deposited on the photographic imaging plate, the deposited ink is then The ink composition is then mixed with the heated blanket and the ink composition on the photographic imaging plate. The image is transferred directly to the heated blanket by direct contact between the A heated blanket is also sometimes called a "thermal blanket." On top of that, the ink particles of the ink composition can be fused into a smooth ink film. The heated blanket can transfer the ink film to the multilayer film. The heated blanket acts as a shock absorber and pressure pad, holding the ink film in place. In a further embodiment, the method further comprises the steps of: The heated blanket transfers the ink film to one or more print layers of the multi-layer film. It is possible.

[0053] In an embodiment, the heated blanket is heated to a temperature of about 100° C. to about 200° C. In some embodiments, the heated blanket may be heated to a temperature between about 100° C. and about 180° C. , about 100℃ to about 160℃, about 100℃ to about 140℃, about 100℃ to about 120℃, about 12 0℃~approx. 200℃, approx. 120℃~approx. 180℃, approx. 120℃~approx. 160℃, approx. 120℃~approx. 140℃, approx. 140℃~approx. 200℃, approx. 140℃~approx. 180℃, approx. 140℃~approx. 160℃ , about 160°C to about 200°C, about 160°C to about 180°C, or about 180°C to about 200°C The material may be heated to a temperature.

[0054] The printing system may include one or more additional steps. In some embodiments, The printing method may not include pre-transfer heating. In some embodiments, the ink composition may be provided in a concentrated form, This may need to be diluted so that the ink composition can be printed. When supplied in concentrated form, the printing method includes providing the concentrated ink composition to an ink supply tank; The concentrated ink composition is diluted and the diluted ink composition is combined with a carrier fluid to form a dispersion in the liquid. forming an ink composition including the charged ink particles.

[0055] Test Method Test methods include: Melt Index (I2) To test the melt index (I2), the ethylene-based polymer samples were Measured according to STM D1238 at 190°C and 2.16 kg. Values ​​are reported in g / 10 min. This corresponds to grams eluted per 10 minutes. Measured according to TM D1238 at 230°C and 2.16 kg.

[0056] density To test density, samples were prepared and measured according to ASTM D4703. and grams per cubic centimeter (g / cc or g / cm 3 ) The measurements are reported as , ASTM D792, Method B, performed within 1 hour of pressing the sample. .

[0057] ASTM D1525 (Vicat softening point) The Vicat softening point is determined when the test specimen is subjected to specified controlled test conditions in accordance with ASTM D1525. When subjected to a load of 10N at a heating rate of 120°C / hour, the specified needle penetration is used to determine the temperature at which

[0058] ASTM 2252-03 (ink fixing) ASTM 2252-03 describes the application of ink or tape to flexible packaging materials. ASTM 225 is a standard test used to evaluate the adhesion of coatings. 2-03 is a flexible adhesive that may not damage the surface when applied and removed from the tape. Can be used for packaging materials. ASTM 2252-03, 3M No. 610 To do this, use Scotch tape, office adhesive tape, or other adhesive known in the field. Tape can be used. For ASTM 2252-03, the tape should be approximately 19mm to 25m long. m (about 3 / 4 inch to 1 inch) wide.

[0059] To perform ASTM 2252-03, first place the sample to be tested on a flat surface. The sample is laid flat and smooth without any wrinkles, creases or folds. Long enough to cover the printed (or coated) area of ​​interest on the sample If testing a large area, several short pieces of tape may be used. The tape should move smoothly and evenly without wrinkling the tape or the sample. The tape is then applied to the sample by pressing the surface of the tape (i.e., with the thumb or index finger). Rub the adhesive (with your finger) to ensure that it is completely adhered to the sample and that there are no air bubbles on the surface. The sample is then held flat against the surface (i.e., with one hand) and the tape is pressed against the Peel at an angle of ~150 degrees (i.e., with the other hand). For each sample tested, The setup time of the cotch tape (the time the tap remains on the sample) must be kept constant. Tape typically travels at speeds of about 305 to 460 mm (12 to 18 inches) per second. It is lifted and pulled back in an even, moderate motion at 100 degrees.

[0060] When the tape is peeled off the sample, the printed or coated gap is visible on the sample. The tape is inspected for any ink or residue that has been removed from the test sample. Coatings are also inspected. To aid in visual inspection, reference standards, i.e. A mutually agreed reference sequence can then be used to determine the extent of transcription. Using a light source, the results are recorded to characterize the degree of adhesion. results may vary from color to color depending on the ink formulation and may be reported as such. There is a match.

[0061] ASTM F904 (adhesive) ASTM F904 is used to perform tests for adhesive strength and heat resistance. To perform ASTM F904, heat or solvents must be applied to separate the plies. The separation is then mechanically initiated. The separated wires of the specimen are then tensile tested using an Instron tensile tester. The grip is then separated and the plies are The force required to separate is defined as the adhesive strength. EXAMPLES

[0062] The following examples are intended to illustrate the features of the present disclosure and are not intended to limit the scope of the disclosure. The following experiments demonstrate the performance of the embodiments of the printing system described herein. The ability was analyzed.

[0063] Example 1 - Preparation of Control Sample, Sample 1, and Comparative Samples A-I Control sample (film with primer) The control sample used was a multilayer film containing a primer. 80% by weight of layer A and 20% by weight of layer B, based on the total weight of the multilayer film. It was a two-layer blown film prepared having the general formula Layer A / Layer B. Layer A was: 80% by weight of ELITE™ 5410 (The Dow (available from the Company, Midland, MI) and 20-fold % of LDPE 219M (The Dow Chemical Company, Mi Layer B comprises a blend of: 100% by weight of DOWLEX® GM 8070 (The Dow Chemical (available from the Imagine Company, Midland, MI). 0.1 to 0.4 grams per square meter (gsm) (DigiPrime, Michel (available from Mann, Inc.) was applied to Layer B prior to printing.

[0064] A control sample was produced using a cast extruder and the following process conditions: [Table 1]

[0065] Sample 1 (multilayer film with printed layer) Sample 1 consisted of 80% by weight of Layer A and 20% by weight of Layer B, based on the total weight of the multilayer film. The films were two layered films prepared having the general formula Layer A / Layer B with B at 0.05%.

[0066] Layer A, the core layer of the multilayer film layer, is comprised of 80% by weight ELIT, based on the total weight of Layer A. E(trademark) 5410 (The Dow Chemical Company, Midla nd, MI) and 20 wt. % LDPE 219M (The Dow Chemical (available from Chemical Company, Midland, MI) Layer B of Sample 1 was approximately 18% vinyl acetate, 2% isobutyl acrylate. , and ethylene acetate with acid and acrylate functionality containing 2% methacrylic acid. It was an acid-vinyl copolymer. Ethylene vinyl acetate with acid and acrylate functional groups. The copolymer was produced by extruding 80% by weight ethylene vinyl acetate polymer at 20°C in a single screw extruder. % by weight of ethylene isobutyl acrylate and methacrylic acid terpolymer at 200°C The ethylene vinyl acetate polymer was prepared for melt blending. It has a melt index of 2 g / 10 min when measured at 190°C and 2.16 kg. The ethylene isobutyl acrylate methacrylic acid terpolymer had a 1 0 g / 10 min melt index and 10 wt. % isobutyl acrylate, and The copolymer had 10% by weight of methacrylic acid.

[0067] Sample 1 film was produced using a cast extruder and the following process conditions: It was done. [Table 2]

[0068] Comparative samples A to I (multilayer films with comparative printed layers) Comparative Samples A-I consisted of 80% by weight of Layer A and Each multilayer film was prepared to have the general formula A / B with 20% by weight of B. Layer A, each multilayer film The core layer of the layer is made of 80% by weight of ELITE™ 5410 (T Available from The Dow Chemical Company, Midland, MI ) and 20% by weight of LDPE 219M (The Dow Chemical Com Layer B of each film contained 100% cellulose acetate (available from Pany, Midland, MI). The composition contained 100 wt. % functionalized with a polar resin according to the composition provided in 3. [Table 3]

[0069] The films were produced using a cast extruder and the following process conditions: [Table 4]

[0070] Example 2 - Performance Analysis of Control Sample, Sample 1, and Comparative Samples A-I In Example 2, the inks were the control sample, as well as Sample 1 and Comparative Sample A. To achieve digital printing, a laser with a voltage difference is used. A laser was used to charge the plate cylinder and create the spectrum of the desired image. Then, ink is applied to the charged cylinder and the ink is deposited where a voltage difference is observed. The ink was dried to remove the carrier. It was then heated on a heating blanket set at 105°C. The ink was transferred to the plate cylinder and the plate cylinder was discharged. The image was thermally transferred using a blanket by adding The ink compositions printed on Samples 1 and Comparative Samples A to I were prepared by Hewlett-Pack. It is commercially available as Electroink from the Card Company.

[0071] Digital printing was completed on the control sample, sample 1, and comparison samples A-I. The 3M tape was used to filter the film in accordance with ASTM 2252-03 as described herein. The ink fixation of the ink cartridge was tested. The results of the ink fixation test, ASTM 2252-03, are shown in Table 5. It is summarized in.

[0072] The adhesive strength of the control sample, sample 1, and comparative samples A to I was also measured by heat sealing. The adhesive strength of the control sample, sample 1, and comparative samples A to I was tested before and after. To test the adhesive properties, each printed film was coated with a solvent-based adhesive, ADCOTE™ 577 (The Dow Chemical Company, Midland, MI) The films were laminated to a biaxially oriented polypropylene film using a 100% polyester resin (available from Epson Corporation). After curing, The adhesive strength was measured before and after heat sealing according to ASTM F904. The results of the adhesive strength of Sample 1, Sample 2, and Comparative Samples A to I are summarized in Table 5. is. [Table 5]

[0073] As shown in the results in Table 5, the control sample, sample 1, comparative sample A, and and Comparative Sample F passed the ink fixation test, ASTM 2252-03, but Samples B to E and G to I failed the test. The control sample, comparative sample A, and comparative sample F have ink compositions in their printed layers. It was shown that the above-mentioned properties can be sufficiently maintained.

[0074] The above results in Table 5 show that when delamination is accelerated, Sample 1 is the control sample, It was further shown to deliver higher adhesion than Sample A and Comparative Sample F.

[0075] Example 3 - Effect of Corona Treatment on Sample 1 and Comparative Sample A In the case of Example 3, Sample 1 and Comparative Sample A are Immediately after the film of Polymer A was produced, it was corona treated in-line at 1-2 kW. To observe the effect of corona treatment on ink adhesion, the film was Sample 1 and Comparative Sample 2 were treated at 1 kW twice as described in Example 2. Ink was digitally printed onto the print layer of Polymer A.

[0076] After the digital printing of the print layers of Sample 1 and Comparative Sample A was completed, the film The ink fixation was tested according to ASTM 2252-03 as described in Example 3. The results of the ink fixation test of corona-treated and untreated sample 1 and comparative sample A were The results are summarized in Table 6. [Table 6]

[0077] As shown in the results in Table 6, corona treatment of Comparative Sample A reduced the Ink fixation was severely affected and the sample failed the tape test. 1 passed the tape test both corona treated and untreated. The results show that the printed layer of sample 1, either corona treated or untreated, absorbs the ink composition sufficiently. The results showed that the sample was not severely affected by the corona treatment, unlike the comparative sample A. This shows that:

[0078] Example 4 - Production of a printed layer containing a blend Samples 2-5 and Comparative Samples J-N (multilayer films with printed layers) In Example 4, a seven-layer film was produced that contained a blend of an ethylene-based polymer and a polar resin. The print layers were tested by constructing films of approximately 100 microns thickness and approximately 1 It had a width of 2 inches (about 30.48 centimeters).

[0079] The layers extruded through extruders G to C were samples 2 to 5 and comparative samples J to N. The same was true for each film. Extruders C, D, and E contained HDPE (The Dow Commercially available from Chemical Company as XUS 59900.94. LDPE (from The Dow Chemical Company) and AGIL Extruders F and G contained 1,2-difluorophenyl ether (commercially available as ITY™ 1021). , DOWLEX(TM) 8070G (The Dow Chemical Compan The films of Samples 2-8 and Comparative Samples J-N were included. The layers are subsequently provided in Tables 7 and 8. [Table 7]

[0080] Samples 2 to 5 and comparative samples J to N have different printing layers and are extruded from extruders A and B. Samples 2 to 5 were extruded from LLDPE (The Dow Chemical (available commercially as DOWLEX™ 8070G from Dowlex Chemical Company), low melt Index Copolymer (VE from The Dow Chemical Company) RSIFY™ 2000), or HDPE (The Dow Commercially available as VERSIFY™ 2000 from Chemical Company The acid and acrylate copolymers were blended with various amounts of ethylene-based polymers containing The copolymer contained ethylene vinyl acetate with acrylate functional groups. The functionalized ethylene vinyl acetate copolymer has acid and acrylate functional groups. Approximately 18% vinyl acetate, 2% isopropyl alcohol, based on the total weight of the ethylene vinyl acetate copolymer. butyl acrylate, and 2% methacrylic acid. Ethylene vinyl acetate copolymer (The Dow Chemical Company) The comparative samples included 100% ethylenediaminetetraacetate (available commercially as ELVAX™ 3128 from Eppendorf Chemical Industries, Ltd.). The printing layer of N is LLDPE (D from The Dow Chemical Company). Samples 2 to 5 and 6 contained 100% cellulose (commercially available as OWLEX® 8070G). The compositions of the printed layers of each of the comparative samples J to N are then provided in Table 8. [Table 8]

[0081] Example 5 - Performance analysis of printed layers containing blends In Example 5, images are of the control sample, as well as samples 2-5 and comparative samples. Digital printing was performed on the printing layers J to N. A laser was used to charge the plate cylinder and generate a spectrum of the desired image. The ink was then applied to the charged cylinder, and the ink was deposited where a voltage difference was observed. The ink was dried to remove the carrier. It was then heated on a heating blanket set at 105°C. The ink was transferred to the plate cylinder and the plate cylinder was discharged. The image was thermally transferred using a blanket by applying a pressure of 1 / 2. Repeat in a loop to mark the control sample as well as samples 2-5 and comparison samples J-N. Digitally printed onto the printing layer.

[0082] The ink compositions are the control sample, samples 2 to 5, and comparative samples J to N. Once the print layer is digitally applied, 3M tape is used to seal the print layer in accordance with ASTM 2252-03. The ink fixation test was carried out on each coating immediately after digital printing. Freshly printed samples, each sample 10 minutes after digital printing, and each sample 60 minutes after digital printing The results of the ink fixation tests are summarized in Table 9. .

[0083] Adhesion strength of the printed layer of the control sample, samples 2 to 5, and comparative samples J to N The temperatures were also tested according to ASTM F904 as described herein. The adhesive strength results of the printed layers of Samples 2 to 5 and Comparative Samples J to N are also summarized in Table 9. is. [Table 9]

[0084] As shown in the results in Table 9, samples 2 and 3 passed the ink fixation test, AST Passed M 2252-03, but samples 4, 5, and comparison samples J~N failed As provided in Table 9, both Samples 2 and 3 had a VA of about 18%, 50 wt.% with acid and acrylate functional groups with 2% iBA and 2% MAA % of ethylene vinyl acetate copolymer. For control samples, the use of primers increases the complexity of the process, Extra cost to add, if inner / outer (wrap seal) seal is required in package design It was apparent that there were drawbacks including poor sealing when

[0085] Modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. It will be apparent that various modifications and variations are possible. More specifically, certain aspects of the present disclosure Although some are identified herein as preferred or particularly advantageous, the present disclosure does not necessarily It is not intended to be necessarily limited to these aspects.

Claims

1. 1. A printing system comprising: an ink composition comprising electrically charged ink particles dispersed in a liquid; and a multilayer film, the multilayer film comprising: a polymer core layer; and one or more printed layers adjacent to said polymeric core layer, said one or more printed layers being The layer is made of at least 50% by weight ethylene vinyl acetate having acid and acrylate functional groups. Copolymer, The acid and acrylate functional ethylene vinyl acetate copolymer is Based on the total weight of ethylene vinyl acetate copolymer having acid and acrylate functional groups , 0.5% to 4% by weight of methacrylic acid or acrylic acid, and 0.5% to 4% by weight of acrylate, 7% to 40% by weight of vinyl acetate, and the balance ethylene. Printing system.

2. The acid and acrylate functional ethylene vinyl acetate copolymer has a molecular weight of 0.8 90g / cm 3 ~0.980g / cm 3 2. The printing system of claim 1, having a density of 。

3. The acid and acrylate functional ethylene vinyl acetate copolymer is Approximately 0.0 ... 0.5 grams (g / 10 min) to about 20.0 g / 10 min. A printing system according to any one of the claims.

4. The acid and acrylate functional ethylene vinyl acetate copolymer is Approximately 1 per 10 minutes when measured at 190°C and 2.16 kg according to M D1238 The prior art has a melt flow rate of about 0.0 grams (g / 10 min) to about 10.0 g / 10 min. A printing system according to any one of the claims.

5. The one or more printed layers further comprise a linear low density ethylene-based polymer.

2. The printing system according to claim 1 .

6. The printing system passes the ink fixation test according to ASTM 2252-03; A printing system according to any one of the preceding claims.

7. The polymer core layer is an ethylene-based polymer having a 2% secant modulus of elasticity greater than 150 MPa.

10. A printing system according to any one of the preceding claims, comprising a polymer.

8. The adhesive layer may further include one or more of a sealing layer, a barrier layer, a tie layer, or a combination thereof. A printing system according to any one of the preceding claims, further comprising:

9. 1. A printing method comprising: transferring the ink composition to a print layer of the multilayer film; the ink composition comprises electrically charged ink particles dispersed in a liquid; The multilayer film comprises a polymeric core layer and one or more polymeric layers adjacent to the polymeric core layer. and a printed layer, the one or more printed layers comprising at least 50% by weight of an acid and an acrylate. The composition comprises an ethylene vinyl acetate copolymer having an acid and an acrylate functional group, The ethylene vinyl acetate copolymer having the acid and acrylate functional groups is 0.5% to 4% by weight of methacrylate based on the total weight of the ethylene vinyl acetate copolymer. acrylic acid, 0.5% to 4% by weight of an acrylate, and 7% to 40% by weight of an acrylic acid or % by weight vinyl acetate and the balance ethylene.

10. The acid and acrylate functional ethylene vinyl acetate copolymer has a molecular weight of 0.8 90g / cm 3 ~0.980g / cm 3 The method of claim 8, wherein the density of the ink is 0.1-0.25 μm.

11. The acid and acrylate functional ethylene vinyl acetate copolymer is Approximately 0.0 ... 0.5 grams (g / 10 min) to about 20.0 g / 10 min.

10. The printing method according to item 8 or 9.

12. The ink composition is transferred directly to the print layer of the multilayer film without a primer. The printing method according to any one of claims 8 to 10,

13. The ink composition is transferred to a printing layer of the multilayer film to produce a print.

12. The method of claim 8, wherein the printed matter passes the ink fixation test according to ASTM 2252-03. The printing method according to any one of claims 1 to 5.

14. The core layer of the multilayer film has a 2% secant modulus of elasticity greater than 250 MPa. The method of printing according to any one of claims 8 to 12, comprising an ethylene-based polymer.

15. The polymer core layer is an ethylene-based polymer having a 2% secant modulus of elasticity greater than 250 MPa. The method of printing according to any one of claims 8 to 14, comprising a polymer.

Citation Information

Patent Citations

  • Imaging media comprising polycarbonate, methods of manufacture, imaging methods, and image-supporting media

    JP2002500782A

  • Multilayer imaging media comprising polypropylene, methods of imaging said media and image bearing media

    JP2003522983A